Short-Term Strategy for Developing School-Based Lesson Study towards Learning Community at Special Education in Indonesia - Bastiana, Bastiana (Universitas Pendidikan Indonesia, 2017)
ABSTRACT: The implementation of Lesson Study provides a new perspective in the context of pedagogy in schools among teachers. This article proposes a short-term strategy that can be implemented in developing School-Based Lesson Study at school towards the establishment of learning community at Special Education. In School-Based Lesson Study, the teachers from various backgrounds have done Lesson Study activities together regardless the subjects they teach. The strategy that can be implemented by the school in the first year is to train the core staffs, to clarify the vision on child education, to have similar perception of teachers, and to create the system of lesson activities. The second and the third year is the time for evaluating the progress of the implementation of School-Based Lesson Study at Special Education based on certain characters, namely the pupils lesson and study from each other, and the teachers learn from each other through meeting in order to improve their teaching skill. KEY WORD: School-Based Lesson Study; Learning Community; Special Education; Short-Term Strategy; Activities Together.Â ABSTRAKSI: â€œStrategi Jangka Pendek untuk Mengembangkan Lesson Studi Berbasis Sekolah Menuju Masyarakat Pembelajar di Sekolah Luar Biasa di Indonesiaâ€. Implementasi Lesson Studi menyediakan perspektif baru dalam konteks pedadogis kepada guru-guru di sekolah. Artikel ini mengusulkan sebuah strategi jangka pendek yang dapat diterapkan dalam mengembangkan Lesson Studi Berbasis Sekolah menuju terbentuknya masyarakat pembelajar di SLB (Sekolah Luar Biasa). Lesson Studi Berbasis Sekolah di mana guru dari berbagai bidang studi bersama-sama melakukan kegiatan Lesson Studi tanpa melihat latar belakang bidang studi yang dipegang oleh guru. Strategi yang diterapkan pada tahun pertama yang dapat dilakukan oleh sekolah adalah membina â€œcore staffâ€ (tenaga inti), mengklarifikasi visi pendidikan anak, menyamakan persepsiÂ unsurÂunsurÂ keahlianÂ guru, dan menciptakan sistem aktivitas pembelajaran. Pada tahun kedua dan ketiga, mengevaluasi tingkat keberhasilan pelaksanaan Lesson Studi Berbasis Sekolah di SLB berdasarkan karakteristik, yaitu anak-anakÂ salingÂ menyimakÂ danÂ salingÂ belajar satuÂ sama lain, dan para guru saling belajar satu sama lain melalui pertemuan untuk mengasah keterampilan mengajar yang kreatif.KATA KUNCI: Lesson Studi Berbasis Sekolah; Masyarakat Pembelajar; Sekolah Luar Biasa; Strategi Jangka Pendek; Aktivitas Bersama.About the Author: Dr. Bastiana is a Lecturer at the Faculty of Education UNM (State University of Makassar) in Makassar City, South Sulawesi, Indonesia. For academic interests, the author is able to be contacted via e-mail address at: bastiana@unm.ac.idHow to cite this article? Bastiana. (2017). â€œShort-Term Strategy for Developing School-Based Lesson Study towards Learning Community at Special Education in Indonesiaâ€ in MIMBAR PENDIDIKAN: Jurnal Indonesia untuk Kajian Pendidikan, Vol.2(2), September, pp.185-196. Bandung, Indonesia: UPI [Indonesia University of Education] Press, ISSN 2527-3868 (print) and 2503-457X (online). Chronicle of the article: Accepted (March 11, 2017); Revised (May 13, 2017); and Published (September 30, 2017).